Spatial Mapping of Coconut Plantation in Airmadidi District, North Sulawesi Using Geographical Information System - Rotinsulu, Wiske; Margaretha, Geby; Pakasi, Sandra (Journal of Agriculture, 2023)
Coconut (Cocos nucifera L.) known by many as the "tree of life is a leading agricultural commodity in North Sulawesi. Coconut is one of the most significant palm crops for both commercial and subsistence use worldwide. Airmadidi District has the potential for plantation land, especially coconut, which is indicated by the area of ??coconut plantation land in Airmadidi in 2021 of 3,373.13 Ha. This research aims to produce spatial mapping of coconut plantation in Airmadidi District using visual interpretation techniques; and to determine the area of ??coconut plantations in Airmadidi District. Visual interpretation method using on screen classification of satelite imagery SPOT 2022 obtained from SAS Planet.  Images were digitized with a geographic information system using ArcGIS 10.8.2 software. The results of the visual interpretation show a map of the distribution of coconut plantations spread across all villages in Airmadidi District, North Minahasa Regency. The total area of coconut plantations in Airmadidi District is 3 023 Ha. Tanggari village has the largest spread of coconut plantations, namely 870,460 Ha, while Sarongsong Satu village has the smallest area, only 2.24 Ha. There was a decrease in the area of coconut plantation during the period of three year which was 305,51 Ha.  The decline in the area of coconut plantations in North Sulawesi, especially in Airmadidi District, is thought to be caused by the conversion of coconut plantation land into residential or industrial areas.